Role of desmoplakin in supporting neuronal activity, neurogenic processes, and emotional-related behaviors in the dentate gyrus - Otsubo, Keisuke; Sakashita, Naoko; Nishimoto, Yuki; Sato, Yo; Tsutsui, Takehisa; Kobayashi, Katsunori; Suzuki, Kanzo; Segi-Nishida, Eri (Frontiers in Neuroscience, 2024)
Desmoplakin (Dsp) is a component of desmosomal cell–cell junctions that interacts with the cadherin complex and cytoskeletal intermediate filaments. In addition to its function as an adhesion component, Dsp is involved in various biological processes, such as gene expression, differentiation, and migration. Dsp is specifically expressed in the hippocampal dentate gyrus (DG) in the central nervous system. However, it is unclear how Dsp impacts hippocampal function and its related behaviors. Using an adeno-associated virus knockdown system in mice, we provide evidence that Dsp in the DG maintains hippocampal functions, including neuronal activity and adult neurogenesis, and contributes to anxiolytic-like effects. Dsp protein is mostly localized in mature granule cells in the adult DG. Dsp knockdown in the DG resulted in a lowered expression of an activity-dependent transcription factor FosB, and an increased expression of mature neuronal markers, such as calbindin. In addition, the suppression of Dsp decreases serotonin responsiveness at the DG output mossy fiber synapses and alters adult neurogenic processes in the subgranular zone of the DG. Moreover, DG-specific Dsp knockdown mice showed an increase in anxiety-like behaviors. Taken together, this research uncovers an unexplored function for Dsp in the central nervous system and suggests that Dsp in the DG may function as a regulator to maintain proper neuronal activation and adult neurogenesis, and contribute to the adaptation of emotion-related behavior.